Comparative economics of conventional, organic, and alternative agricultural production systems - Timothy C. Durham; Tamás Mizik (Economies, 2021)
Agricultural production systems are a composite of philosophy, adoptability, and careful analysis of risks and rewards. The two dominant typologies include conventional and organics, while biotechnology (GM) and Integrated Pest Management (IPM) represent situational modifiers. We conducted a systematic review to weigh the economic merits-as well as intangibles through an economic lens-of each standalone system and system plus modifier, where applicable. Overall, 17,485 articles were found between ScienceDirect and Google Scholar, with 213 initially screened based on putative relevance. Of those, 82 were selected for an in-depth analysis, with 63 ultimately used. Economically, organic generally outperformed conventional systems. This is largely due to their lower production costs and higher market price. However, organic farms face lower yields, especially in the fruit, vegetable, and animal husbandry sectors. With that said, organic farming can provide significant local environmental benefits. Integrated pest management (IPM) is a potentiator of either core system. As a risk reduction and decision-making framework, it is labor intensive. However, this can be offset by input reductions without yield penalty compared to a conventional baseline. Biotechnology is a rapidly emerging production system, notably in developing countries. The use of GM crops results in lower production cost and higher yields. As a conventional modifier, its major advantage is scale-neutrality. Thus, smaller and lower income farmers may achieve higher gross margin. The main source of environmental benefits is reduced pesticide use, which implies a decreased need for fuel and labor. Barring external influences such as subsidies and participation in prescriptive labeling programs, farmers should focus on an a la carte approach (as opposed to discrete system adoption) to optimize their respective enterprises.
Keywords: 330; agriculture; alternative; biotechnology; conventional; ecological; economics; IPM; organic; profitability; sustainability